Inter-regional disparities in emergency department utilization among critically ill patients: A nationwide study from South Korea - Mi Ra Oh; Young Jin Huh; Han Na Lee; Se Hyung Kim; Sung Min Lee (PLoS ONE, 2025)
Background This study examined inter-regional emergency department (ED) utilization among critically ill patients in South Korea and identified demographic, socioeconomic, and system-level factors. Methods A retrospective analysis of 741,701 critically ill ED visits in 2021 was conducted using the National Emergency Department Information System (NEDIS). Inter-regional utilization was defined as receiving care outside the residential emergency medical service (EMS) region. Patient characteristics were compared between inter- and intra-regional groups. Mixed-effects logistic regression, modified Poisson regression, and average marginal effects (AMEs) were applied to identify associated factors. The results were presented concurrently using odds ratios (ORs), adjusted risk ratios (aRRs), and AMEs, including 95% confidence intervals (CIs). Results Overall, 21.7% of critically ill patients received inter-regional care. Male patients had higher odds of inter-regional utilization (OR 1.08, 95% CI: 1.07–1.10; aRRs 1.05, 95% CI: 1.03–1.08), although their absolute probability was significantly lower (AME –8.29%p, 95% CI: –12.42 to –4.16), reflecting differences between relative and absolute measures. Adults aged 19–44 years (OR 1.35, 95% CI: 1.32–1.39) and 45–64 years (OR 1.24, 95% CI: 1.21–1.27) showed higher odds of inter-regional utilization, although corresponding AMEs were not statistically significant. Among older adults, the 65–74-year group showed a non-significant decrease in absolute probability (AME –0.90%p, 95% CI: –3.39 to 1.58), whereas the 75–84-year group demonstrated a significant reduction (AME –5.78%p, 95% CI: –7.64 to –3.92). Pediatric patients also exhibited elevated odds of inter-regional use. Medical Aid beneficiaries had lower relative odds (OR 0.65, 95% CI: 0.63–0.67), and AMEs showed no statistically significant absolute differences. Inter-hospital transfer (OR 1.20, 95% CI: 1.16–1.24) was associated with higher inter-regional use, with a statistically significant increase in absolute probability (AME + 3.74%p, 95% CI: 0.86–6.63). Arrival by ambulance or private vehicle showed positive but non-significant AMEs. High-acuity patients (KTAS 1–2) and those transferred as their final disposition also demonstrated higher relative odds of inter-regional utilization. Conclusions Inter-regional ED utilization was more likely among men, younger and middle-aged adults, high-acuity patients, and those arriving by ambulance or transferred from another hospital, while Medical Aid patients were less likely to receive such care. These findings highlight the importance of strengthening local emergency capacity, optimizing referral and transfer pathways, and implementing region-specific strategies alongside nationwide initiatives.